Study on Shear Behavior of Soil-Structure Interface - Wang, Wei; Lu, Tinghao (Engineering Computation Proceedings, 2009)
Shear behavior of interface between soil and structure plays an important role in the analysis on soil-structure interaction and in the design of disaster prevention and mitigation engineering. In recent years, significant progress has been made in this subject. The current study on interface is reviewed in details, including such aspects as testing study, constitutive model and interface element. Several deficiencies in above mentioned three aspects about interface study are pointed out respectively. The rational way to confirm the thickness of thin-layer interface is proposed, and large-size simple shear tests between different state soils and concrete are recommended to simulate negative friction along the interface, establish perfect constitutive model and confirm its parameters accurately.